2003
DOI: 10.1080/1363849031000097817
|View full text |Cite
|
Sign up to set email alerts
|

Resting energy expenditure and body composition in children with myelomeningocele

Abstract: REE in children with MMC is variable when compared to predicted values. TEE was found to be lower in children with MMC than predicted values and EI was similar to predicted values in this group of seven children. BCM is reduced in children with MMC when compared to expected values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 19 publications
3
20
1
6
Order By: Relevance
“…Among patients with myelomeningocele, 43% were overweight/obese, which is consistent with what other authors, such as Fiore et al 17 and Littlewood et al, 6 have reported. This percentage is higher than the average 31% prevalence observed in different Argentine age groups according to the National Survey on Nutrition and Health (Encuesta Nacional de Nutrición and Salud, ENNyS), 18 but similar to what has been found by other national studies carried out in male and female adolescents.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Among patients with myelomeningocele, 43% were overweight/obese, which is consistent with what other authors, such as Fiore et al 17 and Littlewood et al, 6 have reported. This percentage is higher than the average 31% prevalence observed in different Argentine age groups according to the National Survey on Nutrition and Health (Encuesta Nacional de Nutrición and Salud, ENNyS), 18 but similar to what has been found by other national studies carried out in male and female adolescents.…”
Section: Discussionsupporting
confidence: 82%
“…I n a v e r a g e , o b e s i t y prevalence among patients with myelomeningocele is 42% due to an increased fat mass (FM) combined with an important lean mass (LM) deficit. Obesity may lead to worsening of comorbidities, such as restricted ability to move about, pressure ulcers, and a lower level of autonomy, compromising the quality of life, 6 and metabolic consequences, such as insulin resistance (IR), carbohydrate i n t o l e r a n c e , d i a b e t e s m e l l i t u s , fatty liver, dyslipidemia, arterial hypertension (HTN), obstructive sleep apnea syndrome, and increased cardiovascular risk, among others. 7,8 B e c a u s e o f t h e o r t h o p e d i c pathology described above, it is difficult to make accurate measures …”
Section: Introductionmentioning
confidence: 99%
“…This low lean body mass is primarily due to the absence of the large muscles about the hip and thigh in the LL1 group compared with their less paralyzed peers in groups LL2 and LL3. Investigators (4)(5)(6)(7)(8)(9) have demonstrated that from 40% to 50% of lean body mass is missing in this group with severe paralysis. The loss of lean body mass also helps explain why children with myelomeningocele and significant paralysis become overweight or obese despite low calorie intake (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate weight and low lean body mass causes the CDC/NCHS curves to indicate a low BMI, incorrectly suggesting an undernourished state. Studies using more accurate methods to estimate lean body mass are important to this discussion because they describe lean body mass of approximately 50% of ''normal'' among patients with high levels of paralysis and myelomeningocele (LL1 group) (4)(5)(6)(7)(8)(9). This low lean body mass is primarily due to the absence of the large muscles about the hip and thigh in the LL1 group compared with their less paralyzed peers in groups LL2 and LL3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation